2010
DOI: 10.4317/medoral.15.e526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polyglecaprone 25, Silk and Catgut Suture Materials on Oral Mucosa Wound Healing in Diabetic Rats: An Evaluation of Nitric Oxide Dynamics

Abstract: Objectives: The purpose of this study is to investigate the effects of monocryl (Polyglecaprone 25), silk and catgut suture materials on wound healing in diabetic rats and to evaluate NO (nitric oxide) dynamics. Study desing: Fourty-eight male Wistar-Albino rats weighting 220-270 g were used in this study. The rats were categorized into 2 groups, as control group (n=24) and streptozotocin (STZ) induced diabetic group (n=24). For each group, incision wounds were created on the inner cheeck mucosa of the animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…They found that poliglecaprone 25 and glycomer 631 suture materials were less reactive than polydioxanone in the rat’s skin. In another study, Yilmaz et al [22] performed an experimental study on diabetic rats in order to compare poliglecaprone 25, silk and catgut suture materials on wound healing. They found that although all these suture materials are well tolerated and have enough tensile strength, poliglecaprone 25 seemed to have more beneficial effects on wound healing in diabetic subjects [22].…”
Section: Discussionmentioning
confidence: 99%
“…They found that poliglecaprone 25 and glycomer 631 suture materials were less reactive than polydioxanone in the rat’s skin. In another study, Yilmaz et al [22] performed an experimental study on diabetic rats in order to compare poliglecaprone 25, silk and catgut suture materials on wound healing. They found that although all these suture materials are well tolerated and have enough tensile strength, poliglecaprone 25 seemed to have more beneficial effects on wound healing in diabetic subjects [22].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Yılmaz et al 35 reported that monocryl which is a monofilament suture, created less reaction compared with catgut and silk which are in polyfilament character. In accordance with that study, our results agree with most of the observations made on animals or humans, where silk has been considered as a suture material that induces unwanted tissue reactions.…”
Section: Discussionmentioning
confidence: 99%
“…After achieving an adequate visual field by cleaning the area of operation with an antiseptic solution, using a scalpel (2-mm depth marked) and a 1.5-cm tip mouth spatula, two linear incisional wounds of 1.5 cm, parallel to the occlusal plane, on both right and left buccal mucosa, were made on 5 mm of the upper side of the mucogingival junction [11]. All surgical interventions were performed under clean conditions.…”
Section: Surgical Proceduresmentioning
confidence: 99%